Engineering Pseudomonas putida KT2440 for simultaneous degradation of carbofuran and chlorpyrifos. Issue 6 (15th July 2016) - Gong, Ting; Liu, Ruihua; Che, You; Xu, Xiaoqing; Zhao, Fengjie; Yu, Huilei; Song, Cunjiang; Liu, Yanping; Yang, Chao
Summary: Currently, chlorpyrifos (CP) and carbofuran are often applied together to control major agricultural pests in many developing countries, in most cases, they are simultaneously detected in agricultural soils. Some cost‐effective techniques are required for the remediation of combined pollution caused by multiple pesticides. In this work, we aim at constructing a detectable recombinant microorganism with the capacity to simultaneously degrade CP and carbofuran. To achieve this purpose, CP/carbofuran hydrolase genes and gfp were integrated into the chromosome of a biosafety strain Pseudomonas putida KT2440 using a chromosomal scarless modification strategy with upp as a counter‐selectable marker. The toxicity of the hydrolysis products was significantly lower compared with the parent compounds. The recombinant strain could utilize CP or carbofuran as the sole source of carbon for growth. The inoculation of the recombinant strain to soils treated with carbofuran and CP resulted in a higher degradation rate than in noninoculated soils. Introduced green fluorescent protein can be employed as a biomarker to track the recombinant strain during bioremediation. Therefore, the recombinant strain has potential to be applied for in situ bioremediation of soil co‐contaminated with carbofuran and CP. Abstract : A biosafety strain Pseudomonas putida KT2440 was engineered for simultaneous degradation of CP and carbofuran. The recombinant P. putida KT2440 has potential use in bioremediation of soil co‐contaminated with carbofuran and CP.